Пусть "yx" -- исходное число, т.е. оно представимо в виде 10y + x. Тогда:
{ x + y = 11
{ 10x + y = 10y + x + 63
{ y = 11 – x
{ 9x = 9y + 63
{ 9x = 9(11 – x) + 63
{ 18x = 162
{ y = 2
{ x = 9
Ответ: число 29.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пусть "yx" -- исходное число, т.е. оно представимо в виде 10y + x. Тогда:
{ x + y = 11
{ 10x + y = 10y + x + 63
{ y = 11 – x
{ 9x = 9y + 63
{ y = 11 – x
{ 9x = 9(11 – x) + 63
{ y = 11 – x
{ 18x = 162
{ y = 2
{ x = 9
Ответ: число 29.